2010
DOI: 10.1007/s12206-010-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

A study on the development of photoelastic experimental hybrid method for colour isochromatics (I)

Abstract: Isochromatics obtained from photoelastic experiment shows the stress distributions of the full field of a structure under load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Due to the nature of the geometry of the ring, the extrusion under the compression ratio of 20 % occurred at very low pressures of 0.98 MPa, limiting the application of seals with a square geometry, especially for high‐pressure applications. From earlier research done on O‐ring under the same loading conditions, extrusion was found to occur when the internal pressure was above 3.92 MPa [8]. Therefore the O‐ring may function better under high pressure when compared to the square ring.…”
Section: Experiments Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Due to the nature of the geometry of the ring, the extrusion under the compression ratio of 20 % occurred at very low pressures of 0.98 MPa, limiting the application of seals with a square geometry, especially for high‐pressure applications. From earlier research done on O‐ring under the same loading conditions, extrusion was found to occur when the internal pressure was above 3.92 MPa [8]. Therefore the O‐ring may function better under high pressure when compared to the square ring.…”
Section: Experiments Results and Discussionmentioning
confidence: 90%
“…This research employs the photoelastic experimental hybrid method which combines the merits of analytical, experimental and numerical concepts to analyze the stresses in the seal [6,7]. The hybrid technique of stress analysis has been developed by researchers [7][8][9][10]. In addition to analyz-ing the contact stresses in the square ring, the effects of extrusion on the performance and the dependence of the deformation angle on the applied internal pressure are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For a diametrically compressed compact disk, the methodology of separating the isoclinics is presented by Baek [68]. These drawbacks are removed by the employment of digital photoelasticity [69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…If colour isochromatic data instead of white and black isochromatic data is used in a hybrid method, the hybrid technique can be widely applied to various fields. However, the photoelastic experimental hybrid method of colour isochromatics has been used only for a stress concentration problem [18]. The present research aims to explore the utility of the photoelastic experimental hybrid method for colour isochromatics of crack problems.…”
Section: Introductionmentioning
confidence: 99%